Transplantation of Bone Marrow-Derived Mesenchymal Stem Cells Promotes Delayed Wound Healing in Diabetic Rats - Jiangbo Wan; Liulu Xia; Wenjia Liang; Yi Liu; Qian Cai (Journal of Diabetes Research)
In this paper, we established a delayed wound healing model on diabetic rat to mimic the pathophysiology of clinical patients who suffered from diabetic foot ulcers. We also evaluated if transplantation of allogeneic bone marrow-derived mesenchymal stem cells could promote the delayed wound healing and investigated the possible underlying biological mechanisms and stem cell behavior involved in this process. The results showed that bone marrow-derived mesenchymal stem cells had a positive effect on delayed wound healing in diabetic rats. Intramuscular transplantation demonstrated the best efficacy. This effect is associated with granulation tissue formation, angiogenesis, cellular proliferation, and high vascular endothelial growth factor expression in wound tissues. In addition, bone marrow-derived mesenchymal stem cells have been shown to mobilize and find home for ischemic and wounded tissues to participate in the process of wound healing. Intramuscular transplantation of exogenous isogeneic stem cells may be suitable for clinical application in the treatment of diabetic foot ulcers although the safety of this therapy should be considered.